Experimental investigation of free-running ship manoeuvers under extreme shallow water conditions. (February 2019) - Mucha, Philipp; Dettmann, Thorsten; Ferrari, Victor; el Moctar, Ould
Abstract: We present an experimental investigation of a free-running manoeuvring inland waterway ship at extreme shallow water conditions. Physical tests of zig-zag manoeuvres at two different water depths were performed in model scale and investigated with regards to the effects of limited under-keel clearance. Experimental data comprise results from repeatability studies and may serve for validation of manoeuvring simulations.